Banana Crispy: social media portfolio / Nur Syuhada Ahmad and Nurul Asyiqin Ramli - Ahmad, Nur Syuhada; Ramli, Nurul Asyiqin (2022)
Facebook is a social networking platform that was founded at Harvard University in 2004 and is widely used by people worldwide since it enables us to interact and communicate with family and friends via an internet platform. We have benefited from social media, which was created to link people from all over the world at any time with the use of merely the Internet. Facebook enables entrepreneurs to create online enterprises by advertising, promoting, and even introducing their items to clients. Additionally, it might quickly become the favorite of businesses that were able to precisely target an audience and distribute advertisements directly to those most likely to purchase our products or services. This social networking site features an exceptional feature that is aimed to attract new users. It is solely dependent on Facebook to attract customers and sell its products, as is the case with Banana Crispy, a small internet business. Because of the nature of the internet, online businesses will always have a stronger influence on customer behavior than traditional enterprises. The increasing number of Facebook users on a daily basis necessitates that we take advantage of our easy access to potential buyers by advertising on Facebook. Additionally, consumers prefer to get their needs and requirements online during this Covid-19 pandemic because they are conscious of the dangers of going out during this time. Additionally, because there is no requirement for a physical store, entrepreneurs can maximize revenues. This is because it can save more money and time due to the flexibility of work schedule and the ability to run businesses from any location and at any time. This is since Facebook also offers a mobile application that makes it easier for customers and sellers to communicate with one another. As a result of the numerous advantages of operating an online business, many entrepreneurs choose to do so, resulting in severe rivalry in this industry. A social media portfolio is therefore required by Banana Crispy in order to demonstrate the company's capabilities. As part of this social media portfolio, we have included extensive information on Banana Crispy's Facebook page. This includes certification, the company' introduction, teaser posts, hard-sell posts, and soft-sell posts, among other things. Eventually, we believe Banana Crispy will be successful in the online business world.